KEPUTUSAN PEMBELIAN KOSMETIK PRESPEKTIF EKONOMI ISLAM - Musfiroh, Mila Fursiana Salma (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2024)
Starting with the decision to purchase cosmetics made by female students who have not gone through the selection stage and do not meet the necessary requirements, there is a tendency to prioritize financial capabilities and the short-term effects of using cosmetic products, and the behavior of choosing or using cosmetics is often not commensurate with sufficient knowledge. regarding the selection of appropriate and safe cosmetics. Nowadays, cosmetic consumption is no longer just a necessity, but is influenced by lifestyles and desires that continue to increase and vary. However, female students' awareness of consuming halal products is still lacking and they are not aware of the positive effects. This is caused by a lack of socialization regarding products labeled halal. The aim of the research is to determine the cosmetic purchase decisions of students at the Faculty of Economics and Business (FEB) UNSIQ from an Islamic economic perspective and to determine the factors that influence FEB UNSIQ students in choosing cosmetics. The research method used in this research is a descriptive method with a qualitative approach, using qualitative descriptive data analysis techniques with stages referring to the Miles and Huberman model. The findings of this research reveal that consumer decisions for cosmetics labeled halal among FEB UNSIQ students are higher than for cosmetics that are not labeled halal in accordance with Islamic economics, although there are still some students who use or consume cosmetics that do not have a halal label. The factors that form the basis for using cosmetics for FEB UNSIQ students are personal, psychological, social and cultural. So it can be concluded that students' decisions regarding cosmetics labeled halal are in accordance with the principles of Islamic Economics because they have paid attention to the benefits and considered halal and thayyib aspects when buying cosmetics.